Script Language Guide. Aldus Pagemaker version 5.0 / apple macintosh / microsoft windows . - Pagemaker, Aldus. . (Seattle WA : Aldus Corporation, 1993)
A revised and updated guide for novice and intermediate PageMaker users--IBM or Macintosh. The volume provides a complete introduction to the basic features of PageMaker 5.0, including the program's extensive new control capabilities for using type, graphics, and other page-making elements.
Includes index.
All Ages.
Keywords: Desktop publishing. .; Desktop publishing